2018
DOI: 10.1016/j.hal.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Domoic acid in California sea lion fetal fluids indicates continuous exposure to a neuroteratogen poses risks to mammals

Abstract: Domoic acid (DA) is a neuroexcitotoxic amino acid that is naturally produced by some species of marine diatoms during harmful algal blooms (HABs). The toxin is transferred through the food web from plantivorous fish and shellfish to marine mammals resulting in significant morbidity and mortality. Due to the timing and location of DA producing HABs, it is well documented that pregnant female California sea lions (CSL) are regularly exposed to DA through their diet thereby posing exposure risks to a neuroteratog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…For Rebekah Petroff, who was not involved in the new study, the results are consistent with observations in rodents, 16 , 17 , 18 , 19 marine mammals, 20 , 21 and nonhuman primates. 22 , 23 Petroff, a postdoctoral fellow at the University of Michigan, has studied DomA neurotoxicity in adult crab-eating macaques after low-level exposure.…”
supporting
confidence: 84%
“…For Rebekah Petroff, who was not involved in the new study, the results are consistent with observations in rodents, 16 , 17 , 18 , 19 marine mammals, 20 , 21 and nonhuman primates. 22 , 23 Petroff, a postdoctoral fellow at the University of Michigan, has studied DomA neurotoxicity in adult crab-eating macaques after low-level exposure.…”
supporting
confidence: 84%
“…The data from this study show the reduction in the degree of differentiation of rNSC into all three type of cells and the reduction in axonal length of neurons in the presence of low non-cytotoxic concentration of DA (0.05 μM). Data from rodents and non-human primates have shown that non-cytotoxic low dose exposure to DA during early life was associated with behavioral, memory deficits, and/or structural changes in the brain [47,48,49,50,51,52]. This memory loss may be linked to a reduction and/or the abnormal differentiation of neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our sample size was small, and whilst we had suspected cases of DA exposure in the dam, we did not know what, if any, exposure the solitary pups may have had. A larger study is needed to explore the influence of DA exposure in utero ( Lefebvre et al , 2018 ) and measuring stress-related hormones in hair samples from California sea lions provides a novel method that may prove useful when assessing endocrine function in the dam or exposure to in utero stressors.…”
Section: Discussionmentioning
confidence: 99%